2016
DOI: 10.5500/wjt.v6.i3.548
|View full text |Cite
|
Sign up to set email alerts
|

Current techniques for AB0-incompatible living donor liver transplantation

Abstract: For a long time, it was considered medical malpractice to neglect the blood group system during transplantation. Because there are far more patients waiting for organs than organs available, a variety of attempts have been made to transplant AB0-incompatible (AB0i) grafts. Improvements in AB0i graft survival rates have been achieved with immunosuppression regimens and plasma treatment procedures. Nevertheless, some grafts are rejected early after AB0i living donor liver transplantation (LDLT) due to antibody m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Therefore, this should only be performed when an appropriate conditioning regimen is in place as one study found that, compared to patients with ABO‐compatible liver transplants (n = 1301), patients with ABOi liver transplants (n = 235) who received desensitization protocols, including TPE, had a lower mortality rate (4.7 vs 1.3, respectively; p = 0.007) and no significant difference in graft survival rates (1‐ and 3‐year graft survival rates were 97 and 92% vs 93 and 89%, respectively) . Data from 11 centers revealed their practices for ABOi living donor liver transplants, including avoiding isoagglutinin titers above 64 and closely monitoring patients for AMR in the first 6 weeks posttransplant . While DSAs against human leukocyte antigens (HLA) can cause injury to transplanted livers, expression of Class I HLA antigens can be weaker in livers when compared with other organs, and thus, the culpable HLA antibody patterns may be different …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this should only be performed when an appropriate conditioning regimen is in place as one study found that, compared to patients with ABO‐compatible liver transplants (n = 1301), patients with ABOi liver transplants (n = 235) who received desensitization protocols, including TPE, had a lower mortality rate (4.7 vs 1.3, respectively; p = 0.007) and no significant difference in graft survival rates (1‐ and 3‐year graft survival rates were 97 and 92% vs 93 and 89%, respectively) . Data from 11 centers revealed their practices for ABOi living donor liver transplants, including avoiding isoagglutinin titers above 64 and closely monitoring patients for AMR in the first 6 weeks posttransplant . While DSAs against human leukocyte antigens (HLA) can cause injury to transplanted livers, expression of Class I HLA antigens can be weaker in livers when compared with other organs, and thus, the culpable HLA antibody patterns may be different …”
Section: Resultsmentioning
confidence: 99%
“…PE is considered necessary to maintain a low titer of anti‐ABO antibodies to prevent antibody‐mediated rejection . However, a simplified protocol administering conventional immunosuppressants, rituximab, and IVIg was reported to be able to sufficiently desensitize patients for ABOi LDLT .…”
Section: Discussionmentioning
confidence: 99%
“…The modern era's improved outcomes following ABO‐ILT are attributable to a variety of innovative efforts. The widespread use and improvements in immunosuppression have undoubtedly contributed to better outcomes, with the majority of current protocols, summarized in Table , consisting of steroids, calcineurin inhibitors, and antimetabolites . In 2002, Tanabe et al described a new protocol supplementing systemic immunosuppression, perioperative TPE, and splenectomy with intraportal infusion therapy consisting of methylprednisolone, prostaglandin E1, and gabexate mesylate.…”
Section: Strategies For Risk Mitigationmentioning
confidence: 99%
“…Although infrequently implemented in recent years given high association with catheter‐related problems including hepatic hilar vascular thrombosis, the application of local infusion treatment demonstrated increased patient survival following ABO‐ILT . The advent of extracorporeal therapies, including TPE, DFP, and antigen‐specific immunoadsorption, enable depletion of resident IHs, reducing the chance of AMR . DFP and immunoadsorption have been developed in an attempt to selectively deplete anti‐A and anti‐B IHs void of the disadvantages linked to TPE including hypersensitivity, citrate toxicity, and hemodynamic stress .…”
Section: Strategies For Risk Mitigationmentioning
confidence: 99%
See 1 more Smart Citation